Management of cardiorespiratory function of rabbits by a customized chest drain: An experimental study (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: This study aimed to salvage the study population from the fatality that occurs due to iatrogenic injury to the thoracic cavity’s pleural membrane.  Materials and Methods: An experimental study of temporomandibular joint arthroplasty with costochondral graft was carried out on 72 healthy ‘Oryctolagus cuniculus’ species of male rabbits. The rabbits were distributed into two age groups: growing (3–4 months) and adult (12–18 months). All the procedures were carried out under general anesthesia with xylazine hydrochloride and ketamine hydrochloride after calculating the doses, maintained by halothane and O2 inhalations. Out of 72 rabbits, 33 rabbits had accidental perforation of the pleural membrane observed that required a chest drain.  Results: In this study, 21 (63.64%) rabbits received chest drain and salvaged. The rest of the rabbits (n = 12; 36.36%) that did not receive any chest drain and died. Most of the rabbits (n = 17; 81%) were under the growing group, weighing less than 2 kg and four (19%) were adult rabbits.  Conclusion: This manual chest drain is life-saving for rabbits. It is a new addition to the advancement of thoracic surgery on animals. It is cost-effective and safe. The developed customized drainage system may make it easier to harvest the costochondral graft-related experiments.J. Adv. Vet. Anim. Res., 8(1): 138-145, Mar 2021http://doi.org/10.5455/javar.2021.h496